Stimulating the visit of a physical museum through a virtual one - Loureiro, S. M. C.; Rato, D. (Anatolia, 2024)
Museums are more than a place to preserve collections of pieces. They offer serious leisure activities that can be incremented by using virtual reality tools. Thus, this study aims to analyse (i) the effect of virtual atmospheric cues on serious leisure in a virtual museum environment, and (ii) the impact of serious leisure on the desire to visit the physical museum. Results demonstrated that virtual atmospheric cues exercise a significant effect on the perception of vividness and presence. Both vividness and presence influence serious leisure and this, in turn, affects serious leisure in a virtual museum environment.